TiAlN tribological coatings prepared in industrial deposition system with different rotations - Miletić, Aleksandar; Panjan, Peter; Čekada, Miha; Terek, Pal; Kovačević, Lazar; Škorić, Branko (Advanced Technologies and Materials, 2023)
Efficiency and lifetime of manufacturing tools and mechanical components may be successfully improved by application of thin ceramic coatings. When it comes to tools for machining of hard materials such as machining of hardened steel, TiAlN is one of the most usually applied coatings. This material is of high hardness, high oxidation resistance and high temperature stability. In this research, surface morphology, mechanical and tribological properties of TiAlN coatings prepared in industrial deposition unit were studied. Three different coatings were prepared by selecting different rotational types in a magnetron sputtering deposition chamber. Surface morphology was characterized by stylus profilometry and atomic force microscopy, mechanical properties by nanoindentation technique and Rockwell indentation test, while pin-on-plate test was used to study tribological behavior. It was found that coatings prepared by higher number of rotations are smoother, harder, and more resistant to cracking and wear. These differences are attributed to differences in coating microstructure which refines with increased number of rotations.